Mutagenicity of furan in female Big Blue B6C3F1 mice - Terrell, Ashley N. (2014)
Furan is an abundant food and environmental contaminant that is a potent liver carcinogen in rodent models. To determine if furan is genotoxic in vivo, female B6C3F1 Big Blue transgenic mice were treated with 15 mg/kg bw furan by gavage 5 days a week for 6 weeks, or once weekly for 3 weeks. Liver cII trans-gene mutation-frequency and mutation spectra were determined. Furan did not increase the mutation frequency under either treatment condition. In the 6-week treatment regimen, there was a change in the cII transgene mutation-spectrum, with the fraction of GC to AT transitions significantly reduced. The only other significant change was an increase in GC to CG transversions; these represented a minor contribution to the overall mutation spectrum. A much larger furan-dependent shift was observed in the 3-week study. There was a significant increase in transversion mutations, predominantly GC to TA transversions as well as smaller non-significant changes in GC to CG and AT to TA transversions. To determine if these mutations were caused by cis-2-butene-1,4-dial (BDA), a reactive metabolite of furan, the mutagenic activity and the mutation spectrum of BDA was determined in vitro, in Big Blue mouse embryonic fibroblasts. This compound did not increase the cII gene mutation-frequency but caused a substantial increase in AT to CG transversions. This increase, however, lost statistical significance when adjusted for multiple comparisons. Together, these findings suggest that BDA may not be directly responsible for the in-vivo effects of furan on mutational spectra. Histopathological analysis of livers from furan-treated mice revealed that furan induced multifocal, hepatocellular necrosis admixed with reactive leukocytes and pigment-laden Kupffer cells, enhanced oval-cell hyperplasia, and increased hepatocyte mitoses, some of which were atypical. An indirect mechanism of genotoxicity is proposed in which chronic toxicity followed by inflammation and secondary cell proliferation triggers cancer development in furan-exposed rodents.